Level of functional capacities following soccer-specific warm-up methods among elite collegiate soccer players - Vazini Taher, A.; Parnow, A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Different methods of warm-up may have implications in improving various aspects of soccer performance. The present study aimed to investigate acute effects of soccer specific warm-up protocols on functional performance tests.